NATURE OF LIQUID BITUMENS OF NORTHERN NOVAYA ZEMLYA - Klubov B.A.; Korago Ye.A. (My University, 1990)
The phenomenon described here as first reported in 1993 by Pustovalov from Cape Balashov, Inostrantsev Bay, Novaya Zemlya Island. A 60 m thick member of jointed bituminous sandstone with partings of bituminous shale was found there in several tectonic blocks. Abundant streaks and flows of thick, dark-brown liquid bitumen of the maltha type were seen here in joints of various orientations cutting through limestone and shale, and along the bedding surfaces and in leaching cavities. This article describes the nature of these liquid bitumens.